The Theory of Catallactics, Misapplication in Monetary Policy of Developing Economies and Consequences - SENZU, Emmanuel TWENEBOAH (Journal of Advanced Studies in Finance; Vol 9 No 1 (2018): JASF Volume IX Issue 1(17) Summer 2018, 2018)
It is believed and observed that lack of modern understanding of the economic market of developing countries and it theoretical functioning, is understood to be a contributing factor in affecting quality development and dispensing of monetary policy, resulting in its inability to address desired economic growth per it legal mandate. Which the paper establishes the major factorial phenomenon to be considered, as a means to enhance monetary instrument development and application in such economy.